2013
DOI: 10.1111/1753-0407.12023
|View full text |Cite
|
Sign up to set email alerts
|

Negativation of type 1 diabetes‐associated autoantibodies to glutamic acid decarboxylase and insulin in children treated with oral calcitriol (口服骨化三醇治疗维持儿童1型糖尿病相关的谷氨酸脱羧酶与胰岛素自身抗体阴性)

Abstract: Despite the small number of subjects and the absence of a control group in the present study, 0.25 μg/day calcitriol effectively negativates anti-GAD65 antibodies and IAA after a median time of 6 months. This simple, safe, and low-cost strategy may prove effective in the prevention of T1D in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Higher doses of cholecalciferol (2000 IU/day, 4000 IU/day, 70 IU/Kg/day, or 14000 IU/month) improved the immunity status in small populations with T1DM [ 386 – 389 ]. Similar data were obtained with calcidiol for 1 year or calcitriol for 6 months in two pilot studies [ 390 , 391 ].…”
Section: Extraskeletal Actions Of Vitamin Dsupporting
confidence: 82%
“…Higher doses of cholecalciferol (2000 IU/day, 4000 IU/day, 70 IU/Kg/day, or 14000 IU/month) improved the immunity status in small populations with T1DM [ 386 – 389 ]. Similar data were obtained with calcidiol for 1 year or calcitriol for 6 months in two pilot studies [ 390 , 391 ].…”
Section: Extraskeletal Actions Of Vitamin Dsupporting
confidence: 82%
“…Intervention studies with different doses of vitamin D 3 in autoimmune diseases lead to different outcomes, recently we demonstrated that a bolus of vitamin D 3 (300,000 UI) in patients affected by early rheumatoid arthritis is effective in ameliorating general health, however, we found no effect on disease activity nor on inflammatory markers and T cells subset [ 73 ]. In patients affected by type 1 diabetes clinical intervention studies with vitamin D 3 or hydroxylated analogs have been disappointing, as no clinical study has demonstratedan effect of vitamin D in ameliorating glucose metabolism and insulin secretion [ 113 , 114 ], however, in a small prospective trial in children with type 1 diabetes autoantibodies 1,25(OH) 2 D 3 administration decreased the serum glutamic acid decarboxylase 65 (GAD65) autoantibody, pointing to some immunomodulation of 1,25(OH) 2 D 3 [ 115 ].…”
Section: Vitamin D and Autoimmune Diseasesmentioning
confidence: 99%
“…However, in all the above studies, the vitamin D dose used was particularly low, inadequate even for prophylaxis from hypovitaminosis D, even more so to except a therapeutic effect and the duration too short to show results based on immunomodulation driven by a presumed rise in 1–25 OHD3 levels. Knowing that 25(OH) vitamin D suppresses macrophage adhesion and migration [ 20 ], we decided to use the active hormone calcitriol, whose immunomodulating properties have been shown even in negativating type 1 diabetes-associated autoantibodies [ 21 ], while properly substituting with 4000 IU cholecalciferol daily assured optimal (>40 ng/mL) 25 OHD levels [ 22 ], without any risk for overdosing [ 23 ].…”
Section: Discussionmentioning
confidence: 99%